The effects of self-acupressure on fatigue and sleep quality in individuals diagnosed with epilepsy: a randomised controlled trial - Gulcan, Bahcecioglu Turan; Kutlu, Gulya (Academic Press Inc Elsevier Science, 2025)
Aim: This research investigates the impact of self-administered acupressure on the sleep quality and fatigue levels of individuals diagnosed with epilepsy. Method: A randomized controlled trial was carried out between September 2022 and July 2023 with 60 epilepsy patients, equally divided into intervention and control groups. Participants in the intervention group engaged in self-acupressure sessions over a four-week period, twice weekly-once in the morning and once in the afternoon. Each session lasted 18 min and targeted four specific acupressure points. The control group received no intervention. Data were gathered using a Descriptive Information Form, the Piper Fatigue Scale, and the Pittsburgh Sleep Quality Index (PSQI). Results: After the intervention, patients in the self-acupressure group showed significant reductions in PSQI total score (d = 1.524) and subdomains: subjective sleep quality (d = 0.865), sleep latency (d = 0.990), sleep duration (d = 0.694), habitual sleep efficiency (d = 0.735), sleep disturbances (d = 0.678), use of sleep medication (d = 1.077), and daytime dysfunction (d = 1.129), compared to the control group. Similarly, significant reductions were observed in Piper Fatigue Scale total score (d = 0.997) and subdomains: Behavioral/Severity (d = 0.589), Affective (d = 0.935), Sensory (d = 0.845), and Cognitive/Mood (d = 0.884). Conclusion: Self-acupressure has positive effects on sleep quality and fatigue in individuals with epilepsy. Nurses should encourage self-acupressure in epilepsy management. It is an inexpensive and easily accessible method.
Keywords: Epilepsy; Nurse fatigue; Sleep quality; Self-acupressure